2023
DOI: 10.3389/fcimb.2023.1229284
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of OXA-232-producing carbapenem-resistant Klebsiella pneumoniae ST15 in a Chinese teaching hospital: a molecular epidemiological study

Xiaoyan Wu,
Xiangchen Li,
Junjie Yu
et al.

Abstract: Background and AimsThe incidence of OXA-232-producing carbapenem-resistant Klebsiella pneumoniae (CRKP) has been on the rise in China over the past five years, potentially leading to nosocomial epidemics. This study investigates the first outbreak of CRKP in the Second Affiliated Hospital of Jiaxing University.MethodsBetween February 2021 and March 2022, 21 clinical isolates of OXA-232-producing CRKP were recovered from 16 patients in the Second Affiliated Hospital of Jiaxing University. We conducted antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
1
1
Order By: Relevance
“…Although previous studies have commonly found the clonal spread of CRKP in neurology and intensive care units (ICU) (Wu et al, 2023), our research findings indicates that the primary distribution of CRKP is within respiratory medicine. This finding highlights the importance of the use of invasive devices, whether tracheal intubation or other forms, in the transmission of CRKP.…”
Section: Discussioncontrasting
confidence: 63%
“…Although previous studies have commonly found the clonal spread of CRKP in neurology and intensive care units (ICU) (Wu et al, 2023), our research findings indicates that the primary distribution of CRKP is within respiratory medicine. This finding highlights the importance of the use of invasive devices, whether tracheal intubation or other forms, in the transmission of CRKP.…”
Section: Discussioncontrasting
confidence: 63%
“…C1 and C4 displayed higher virulence, likely contributing to the severity of infections they cause. Recently, numerous nosocomial outbreaks of ST15 Kpn were reported in the YRD region including Hangzhou, Lishui, Wenzhou, Yancheng, Jiaxing and Shanghai ( Li et al, 2019 ; Jia et al, 2021 ; Zhu Z. et al, 2021 ; Huang et al, 2022 ; Wu et al, 2023 ; Zhang et al, 2023 ). The YRD region is one of the most economically active regions in China and attracts a large number of migrant workers from Yunnan, Sichuan, and Anhui provinces every year.…”
Section: Discussionmentioning
confidence: 99%